Upaya Pemerintah Desa dalam Meningkatkan Partisipasi Masyarakat dalam Pelaksanaan Tradisi Marsiadapari di Desa Manalu Kecamatan Parmonangan Kabupaten Tapanuli Utara - Manalu, Ovi Erlinda; Susanti, Sani (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to understand the efforts of the Village Government in increasing community participation in the implementation of the Marsiadapari tradition in Manalu Village, Parmonangan District, North Tapanuli Regency. The type of research used is descriptive qualitative research. The subjects in the study amounted to 4 people. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques included data reduction, data presentation, and conclusion drawing. The research results show that the Village Government has made various preventive efforts, such as socialization and counseling through village meetings and involving community leaders. One of the main approaches taken is collaboration with traditional leaders, who have an in-depth understanding of the procedures and meanings of the Marsiadapari tradition. These preservative efforts are important to maintain the authenticity and continuity of the Marsiadapari tradition. Additionally, curative efforts have also been made by providing superior seeds, free fertilizers, and agricultural equipment that can be borrowed by the community and organizing cultural events such as Marsiadapari tor-tor performances. The Village Government also undertakes adaptive efforts by encouraging the use of environmentally friendly agricultural technology and developing alternative activities that are in line with the social and economic conditions of the community, so that the Marsiadapari tradition remains relevant in the modern era.